Downregulated eosinophil activity in ulcerative colitis with concomitant primary sclerosing cholangitis. Issue 1 (30th March 2018) - Lampinen, Maria; Fredricsson, Annika; Vessby, Johan; Martinez, Johana Fernandez; Wanders, Alkwin; Rorsman, Fredrik; Carlson, Marie
Abstract: Primary sclerosing cholangitis (PSC) is a chronic bile duct inflammation strongly connected to ulcerative colitis (UC). PSC is associated with an increased risk of colon cancer, but the link between the intestinal and the bile duct inflammation is still unknown. Also, the involvement of intestinal immune cells in the pathogenesis of PSC remains to be determined. The eosinophil granulocyte is one of the immune cells implicated in the inflammatory process of ulcerative colitis. This study was performed to determine how the accumulation and activation of intestinal eosinophils may differ between UC with and without concomitant PSC, and how this may be influenced by the cytokine/chemokine profile of the intestinal compartment. Eosinophils from peripheral blood and multiple parts of the colon were analyzed by flow cytometry. The intestinal level of inflammatory mediators was assessed using a multiplex proximity extension assay and a quantitative immunoassay. We found that colonic eosinophils were more abundant in both UC and PSC‐UC compared with controls, but that their expression of activation markers was significantly increased in UC only. The colonic level of pro‐inflammatory cytokines was increased in active UC but not in PSC‐UC. In conclusion, we show for the first time that eosinophil activation phenotype discriminates between UC and PSC‐UC, and that this may depend on the local cytokine profile of the colonic mucosa. Abstract : Lower expression of activation markers on eosinophils in UC with concomitant PSC may depend on the local protein profile of the colonic mucosa.